Occurrence of Salmonella spp. and E.coli isolates from peridomestic cockroaches (Periplaneta americana) and their antibiotic susceptibility patterns - Meor Abdullah, Nurliyana (2016)
Cockroaches are abundant in Malaysia and are seen to harbour an array of pathogens. Environmental and sanitary conditions associated with demographic/socio-economic settings of an area could contribute to the prevalence of disease pathogens in cockroaches. The aim of this study was to determine the incidence of bacteria of public health interest transmitted by cockroaches in different environments. From 11th January to 17th January 2016, cockroaches were trapped in 4 different areas i.e. Serdang, Dengkil and Kajang. A total of 40 cockroaches were collected in all areas. The cockroach species of interest were identified to be the common peridomestic cockroaches (Periplaneta americana). A total 40 external body surface and 40 gut homogenates of the cockroaches were analysed for Salmonella (S) and Escherichia coli (EC), and subjected to antibiotic susceptibility test (AST). The external body surface and gut homogenates samples were streaked onto special agars and incubated for isolation of the specific bacteria. After the bacteria were identified, they were then subjected to AST using standard Kirby Beuer Method (Disk diffusion). The status of resistance were measured using Zone of Inhibition. Results from this study showed that 6 out 80 specimens of cockroaches analysed harboured S spp. which comprised of 5% recovered from external body surfaces and 10% from gut contents. For EC, a total of 22 out of 80 specimens were confirmed as EC isolates which comprised of 42.5% recovered on external body surfaces and 12.5% from gut contents. Salmonella spp. were found in all cockroaches caught from all areas except those trapped in a student room, Faculty of Veterinary Medicine and college 17, UPM. The occurrence of S spp. from all samples studied was low. Samples with EC were mostly analysed from cockroaches collected from squatters and mini market. Both S and EC isolates in this study were found to be multi-drug-resistant (MDR) to antibiotics used in human. Among the 6 S spp. isolates, one of them was found to be MDR positive whereas for EC, 5 out of 22 isolates were found to be MDR positive. Results from this study confirmed that cockroaches were carrier for a number of bacterial species especially S and EC, and these bacteria were found to be resistant to some antibiotics. The prevalence and burden of infection in cockroaches is likely to be a reflection of the sanitary conditions of these areas. Also, cockroaches in these areas making incursions in homes may increase the risk of human infections with these disease agents. To ensure adequate elimination of these microorganisms in specific environments, the control of cockroaches appears to be fundamental.